The Modifications of Haemoglobin, Erythropoietin Values and Running Performance While Training at Mountain vs. Hilltop vs. Seaside - Maria Cristina Man; Cătălin Ganera; Gabriel Dan Bărbuleț; Michał Krzysztofik; Adelina Elena Panaet; Alina Ionela Cucui; Dragoș Ioan Tohănean; Dan Iulian Alexe; Ioana Maria Curițianu (MDPI, 2021)
Altitude training increases haemoglobin, erythropoietin values among athletes, but may have negative physiological consequences. An alternative, although less explored, that has the potential to positively influence performance while avoiding some of the negative physiological consequences of hypoxia is sand training. Ten endurance-trained athletes (age: 20.8 ± 1.4, body mass: 57.7 ± 8.2 kg, stature: 176 ± 6 cm; 5000 m 14:55.00 ± 0:30 min) performed three 21-day training camps at different locations: at a high altitude (HIGH), at the sea-level (CTRL), at the sea-level on the sand (SAND). Differences in erythropoietin (EPO) and haemoglobin (Hb) concentration, body weight, VO2max and maximal aerobic velocity (VMA) before and after each training cycle were compared. Data analysis has indicated that training during HIGH elicited a greater increase in VO2max (2.4 ± 0.2%; p = 0.005 and 1.0 ± 0.2%; p < 0.001) and VMA (2.4 ± 0.2%, p < 0.001 and 1.2 ± 0.2%; p = 0.001) compared with CTRL and SAND. While increases in VO2max and VMA following SAND were greater (1.3 ± 0.1%; p < 0.001 and 1.2 ± 0.1%; p < 0.001) than those observed after CTRL. Moreover, EPO increased to a greater extent following HIGH (25.3 ± 2.7%) compared with SAND (11.7 ± 1.6%, p = 0.008) and CTRL (0.1 ± 0.3%, p < 0.001) with a greater increase (p < 0.01) following SAND compared with CTRL. Furthermore, HIGH and SAND elicited a greater increase (4.9 ± 0.9%; p = 0.001 and 3.3 ± 1.1%; p = 0.035) in Hb compared with CTRL. There was no difference in Hb changes observed between HIGH and SAND (p = 1.0). Finally, athletes lost 2.1 ± 0.4% (p = 0.001) more weight following HIGH vs. CTRL, while there were no differences in weight changes between HIGH vs. SAND (p = 0.742) and SAND vs. CTRL (p = 0.719). High-altitude training and sea-level training on sand resulted in significant improvements in EPO, Hb, VMA, and VO2max that exceeded changes in such parameters following traditional sea-level training. While high-altitude training elicited greater relative increases in EPO, VMA, and VO2max, sand training resulted in comparable increases in Hb and may prevent hypoxia-induced weight loss.
-
Keywords: altitude; haemoglobin; erythropoietin; hypoxia; endurance; sand